EKSISTENSI ORGANISASI KEMASYARAKATAN (ORMAS) DALAM PARTAI POLITIK DI KECAMATAN SUKAWATI - I Wayan Putra Widia Sukma (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThe research was conducted in the districts Sukawati aimed to determine (1) the extent of the involvement of community-based organizations (CBOs) in the party in the district Sukawati (2) the strategy undertaken by community organizations (CBOs) to enter the political parties in the district Sukawati (3 ) constraints faced by community organizations (CBOs) in engagement with the political parties in the district Sukawati. The subject in this study are : (a) members of civil society organizations (CBOs) (b) members of a political party (c) community leaders and the public. This study used qualitative research methods deskipif and data collection, the authors use observation techniques, interviewing and recording dokumen.Serta in this qualitative descriptive study, researchers used qualitative data analysis, which is a research procedure that produces descriptive data in the form of words written or spoken of the people and the behavior observed by the sampling method (sampling purfursip). The results of this study were (1) the involvement of community-based organizations (CBOs) in the party so far seen in (a) providing escorts in the activities of political parties (b) participate in the meeting invitation attend political party (c) provide and find support for party members political (d) establish forms of cooperation or agreement between members of civil society organizations (CBOs) with members of political parties (e) erection attributes by community organizations (CBOs) and political parties. (2) Strategies undertaken by community organizations (CBOs) to enter into a political party that is (a) because of the proximity of one of the members of civil society organizations (CBOs) with members of the party that leads to all members of the community-based organizations (CBOs). (3) the constraints faced by community-based organizations (CBOs) in engagement with the political party that is (a) hard members of civil society organizations (CBOs) to refuse an invitation from members of the political party (b) the difficulty of civil society organizations (CBOs) to agree on a cooperative agreement (c) the space for civil society organizations (CBOs) to be very limited (d) the difficulty of members of civil society organizations (CBOs) in our society gain the trust of the public.Key words: The existenceand activities ofcivil society organizations (CBOs) in